Parametric study on the regeneration heat requirement of an amine-based solid adsorbent process for post-combustion carbon capture - Zhang, Wenbin; Liu, Hao; Sun, Yuan; Cakstins, Janis; Sun, Chenggong; Snape, Colin E. (Elsevier, 2016)
The thermal energy required for regeneration of CO2-rich adsorbents or absorbents is usually regarded as the most important criterion to evaluate different materials and processes for application in commercialscale CO2 capture systems. It is expected that the regeneration heat can be greatly reduced by replacing the mature aqueous monoethanolamine (MEA) technology with amine-based solid adsorbents capturing systems, due to the much lower heat capacity of solid adsorbents comparing to aqueous MEA and the avoidance of evaporating a large amount of water in the regenerator. Comparing to the MEA technology, the regeneration heat for solid adsorbent based systems has not received adequate attention especially on the impacts of process related parameters. Further, the methodologies used in previous investigations to calculate the regeneration heat may have deficiencies in defining the working capacities, adopting proper heat recovery strategies and/or evaluating the effect of moisture co-adsorption. In this study, an energy equation to calculate the regeneration heat has been revised and proposed to systematically evaluate the most important parameters affecting the regeneration heat, including the physical properties of the adsorbents and process related variables including the heat of adsorption, specific heat capacity, working capacity, moisture adsorption of the polyethyleneimine (PEI)/silica adsorbent, the swing temperature difference and the degree of heat recovery. Based on the parametric analysis, the calculated regeneration heat for the PEI/silica adsorbent based system is found to be around 2.46 GJ/tCO2, which is much lower than the value of 3.9 GJ/tCO2 for a typical aqueous MEA system and is also lower than 3.3 GJ/tCO2 for an advanced MEA system. Sensitivity analysis of all the parameters has also been conducted and the results have shown that working capacity, moisture adsorption and heat recovery ratios are the most influential factors. With more proficiency and development in the energy efficient process designs, the advantages of a solid adsorbent based capturing system over typical MEA systems will be justified.